2012
DOI: 10.1182/blood-2011-12-395772
|View full text |Cite
|
Sign up to set email alerts
|

Smad2/Smad3 in endothelium is indispensable for vascular stability via S1PR1 and N-cadherin expressions

Abstract: Transforming growth factor-␤ (TGF-␤) is involved in vascular formation through activin receptor-like kinase (ALK)1 and ALK5. ALK5, which is expressed ubiquitously, phosphorylates Smad2 and Smad3, whereas endothelial cell (EC)-specific ALK1 activates Smad1 and Smad5. Because ALK5 kinase activity is required for ALK1 to transduce TGF-␤ signaling via Smad1/5 in ECs, ALK5 knockout (KO) mice were not able to give us the precise mechanisms by which TGF-␤/ALK5/Smad2/3 signaling is implicated in angiogenesis. To delin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
53
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(57 citation statements)
references
References 33 publications
4
53
0
Order By: Relevance
“…Consistent with this, it was recently shown that endothelial cell-specific Smad2/Smad3 double mutants develop similar brain hemorrhage (Itoh et al, 2012). Although this report did not characterize brain vascular sprouting/branching, it is interesting to point out that S1pr1 mRNA expression was downregulated in Smad2/Smad3 mutants (Itoh et al, 2012), and endothelial cellspecific S1pr1 mutants (like Itgb8, Tgfb1, Tgfbr2 and Alk5 mutants) develop endothelial cell hypersprouting before hemorrhage (Gaengel et al, 2012). It is now important to determine how αVβ8-TGFβ signaling interacts with other pathways, including VEGF, Notch, BMP and S1PR1, known to regulate sprouting angiogenesis.…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations
“…Consistent with this, it was recently shown that endothelial cell-specific Smad2/Smad3 double mutants develop similar brain hemorrhage (Itoh et al, 2012). Although this report did not characterize brain vascular sprouting/branching, it is interesting to point out that S1pr1 mRNA expression was downregulated in Smad2/Smad3 mutants (Itoh et al, 2012), and endothelial cellspecific S1pr1 mutants (like Itgb8, Tgfb1, Tgfbr2 and Alk5 mutants) develop endothelial cell hypersprouting before hemorrhage (Gaengel et al, 2012). It is now important to determine how αVβ8-TGFβ signaling interacts with other pathways, including VEGF, Notch, BMP and S1PR1, known to regulate sprouting angiogenesis.…”
Section: Discussionsupporting
confidence: 73%
“…The effects of αVβ8-TGFβ1 appear to be directed to endothelial cells, not the neuroepithelium, because endothelial cell-specific Tgfbr2 and Alk5 mutants phenocopy Itgb8 mutants, and neuroepithelial cell-specific deletion of Tgfbr2 exhibited no vascular phenotype. Consistent with this, it was recently shown that endothelial cell-specific Smad2/Smad3 double mutants develop similar brain hemorrhage (Itoh et al, 2012). Although this report did not characterize brain vascular sprouting/branching, it is interesting to point out that S1pr1 mRNA expression was downregulated in Smad2/Smad3 mutants (Itoh et al, 2012), and endothelial cellspecific S1pr1 mutants (like Itgb8, Tgfb1, Tgfbr2 and Alk5 mutants) develop endothelial cell hypersprouting before hemorrhage (Gaengel et al, 2012).…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…Our findings, together with the findings of Clavin and co-workers, imply that FGF2-meditated maintenance of LEC characteristics might be important for functional lymphatic regeneration during tissue repair in vivo. Recent studies have reported that endothelial-cell-specific knockout mice for Fgfr1 or Smad2 are viable (Itoh et al, 2012;Zhao et al, 2012), suggesting that both genes, and their potential roles in lymphatic EndMT are dispensable for developmental lymphangiogenesis and lymphatic vessel function under physiological conditions. However, it would be important to examine whether these mice exhibit defects in lymphatic vessel regeneration and function during wound healing, and whether and how FGFR, Ras and TGFb signalling contribute to lymphatic regeneration and function in vivo.…”
Section: Discussionmentioning
confidence: 99%